Temperature-Dependent Exciton Dynamics in a Single GaAs Quantum Ring and a Quantum Dot - Kim, Heedae; Kim, Jong Su; Song, Jin Dong (MDPI, 2022)
Micro-photoluminescence was observed while increasing the excitation power in a single GaAs quantum ring (QR) at 4 K. Fine structures at the energy levels of the ground (N = 1) and excited (N = 2) state excitons exhibited a blue shift when excitation power increased. The excited state exciton had a strong polarization dependence that stemmed from the asymmetric localized state. According to temperature-dependence measurements, strong exciton-phonon interaction (48 meV) was observed from an excited exciton state in comparison with the weak exciton-phonon interaction (27 meV) from the ground exciton state, resulting from enhanced confinement in the excited exciton state. In addition, higher activation energy (by 20 meV) was observed for the confined electrons in a single GaAs QR, where the confinement effect was enhanced by the asymmetric ring structure.